Karakterisasi Alginat Dari Ganggang Coklat ( Sargassum crassifolium, Mont ) Dengan Menggunakan CaCl2 14 % - Auzal Halim; Yeni Novita Sari; Maria Dona Octavia (Jurnal Farmasi Higea, 2011)
Analysis of the synthetic sweetener sodium saccharin and sodium cyclamate in tea packaging has been done. The content of synthetic sweeteners are identified by color reactions and test microcrystals. The results obtained were compared with the reference standard material. Of the four samples tested, obtained three samples containing sodium cyclamate, while the other samples did not contain sodium cyclamate and sodium saccharin. Levels are determined by sodium cyclamate spektrofoto, ether UV-Vis. Levels of sodium cyclamate were obtained not exceed the maximum limit allowed by the Ministry of Health of the Republic of Indonesia is 0.3% for soft drinks.